Analysis of gravity-driven normal faults using a 3D seismic reflection dataset from the present-day shelf-edge break of the Otway Basin, Australia. Issue 1 (1st December 2016) - Robson, Alexander; King, Rosalind; Holford, Simon
Abstract : The growth, interaction and controls of gravity-driven normal faults is somewhat understudied. Using three-dimensional (3D) and two-dimensional (2D) seismic reflection data, located at the present-day shelf-edge break and into the deepwater province of the Otway Basin, southern Australia, we aim to temporally and spatially constrain the development of a normal fault system and determine the controls on growth. The Otway Basin is a Late Jurassic to Cenozoic age, rift-to-passive margin basin. The seismic reflection data images a gravity-driven fault array, consisting of ten fault segments, striking NW-SE (128-308), located within Upper Cretaceous clastic sedimentary rock. We analyse the growth of a gravity-driven hard-linked fault assemblage interacting with basement normal faults. Our analysis shows that the fault assemblage is linked to major basement faults and displays Turonian-Santonian nucleation, continued growth until the latest-Maastrichtian and a maximum throw of 1.74 km. High variability of throw along-strike and down-dip of the fault assemblage indicates growth via lateral and vertical segment linkage. We interpret that the spatial and temporal evolution of the fault assemblage is the result of rifting basement fault control during Upper Cretaceous resumed crustal extension in the Otway Basin. The control of the rifting basement faults on these gravity-driven normal faults has implications towards the growth and petroleum prospectivity of gravity-driven normal faults on passive margins such as the Niger Delta and Gulf of Mexico, but also towards gravity-driven normal faults developed in supra-salt sedimentary rock in rift basins, such as the North Sea and Suez Rift.